The comparison of physical fitness in secondary male students in altitude and coastal areas - Esmaeil Zahıbı; Seyed Hossein Alavı (Türk Spor ve Egzersiz Dergisi)
The aim of this research is the comparison of physical fitness in secondary male students in altitude and coastal areas and difference between the physical fitness on based AAHPERD test. The samples consist of 450 subjects of 1017 subjects in altitude (Shahrekord) and coastal area (Mahmood Abad) in Iran in years of 2013 which were selected cluster- randomly sampling by Morgan Table. We investigated the effect of high altitude on the tests of physical fitness resident students near sea level (-5 m) and in Altitude (2100 m). The tests of physical fitness include: Pull-ups test, Sit-ups test, Agility test (4 x 9), 45 Sprint test, 1600m running, Long jump and Flexibility test. For determining of different between physical fitness of altitude and coastal area students was used t- test. The result of this research shows that there is no significant difference between the average of Pull-ups test (t=0.965; p=0.385), Flexibility (t=1.722; p=0.089), Agility (4 x 9 m) test (t=1.765; p=0.084) and 45 sprint (t=1.24; p=0.221) of students in coastal area and altitude. There is significant difference between the average of Sit-ups (t=2.29; p=0.016), 1600m running (t=11.132; p=0.001) and Long jump (t=3.18; p=0.004) in altitude. The students of altitude have higher power and cardio-respiratory endurance rather than coastal area. But the students of coastal area have stronger abdominal muscles rather than altitude. High altitude reduces the distance covered by youth athlete students during tests. Neither acclimatization nor lifelong residence at high altitude protects against detrimental effects of altitude on tests activity profile.